Karay (Karaim) language online conversational courses for foreigners - Kocaoğlu, Timur (Vilnius University Proceedings, 2024)
This paper gives information on the purpose and the contents of the Karay (Karaim) Language Online Conversational Courses for Foreigners, held between September and December in 2022. This course was joined by around 45 voluntary participants from various countries in Europe, Asia, and the USA. Two native speakers of Karay also helped this course participants by providing them with the correct pronunciation of the Karay literary language.
Keywords: Karay (Karaim); online; conversations; literature; culture